Biomass-Derived P/N-Co-Doped Carbon Nanosheets Encapsulate Cu3P Nanoparticles as High-Performance Anode Materials for Sodium–Ion Batteries - Yin, Yanyou; Zhang, Yu; Liu, Nannan; Sun, Bing; Zhang, Naiqing (Frontiers in Chemistry, 2020)
Biomass-derived approaches have been accepted as a practical way for the design of transitional metal phosphides confined by carbon matrix (TMPs@C) as energy storage materials. Herein, we successfully synthesize P/N-co-doped carbon nanosheets encapsulating Cu3P nanoparticles (Cu3P@P/N-C) by a feasible aqueous reaction followed by a phosphorization procedure using sodium alginate as the biomass carbon source. Cu-alginate hydrogel balls can be squeezed into two-dimensional (2D) nanosheets through a freeze–drying process. Then, Cu3P@P/N-C was obtained after the phosphorization procedure. This rationally designed structure not only improved the kinetics of ion/electron transportation but also buffered the volume expansion of Cu3P nanoparticles during the continuous charge and discharge processes. In addition, the 2D P/N co-doped carbon nanosheets can also serve as a conductive matrix, which can enhance the electronic conductivity of the whole electrode as well as provide rapid channels for electron/ion diffusion. Thus, when applied as anode materials for sodium-ion batteries, it exhibited remarkable cycling stability and rate performance. Prominently, Cu3P@P/N-C demonstrated an outstanding reversible capacity of 209.3 mAh g−1 at 1 A g−1 after 1,000 cycles. Besides, it still maintained a superior specific capacity of 118.2 mAh g−1 after 2,000 cycles, even at a high current density of 5 A g−1.